Pulmonary rehabilitation in patients with chronic obstructive pulmonary disease - Ćirić Zorica; Stanković Ivana; Rančić Milan; Pejčić Tatjana; Radović Milan (Vojnosanitetski Pregled)
Background/Aim. Chronic obstructive pulmonary disease (COPD) irreversibly damages pulmonary function leading to disorder of arterial blood gases, arterial partial pressure of oxygen (PaO2) and arterial partial pressure of carbon dioxide (PaCO2), appearance of dyspnea, and decrease of physical condition. The aim of this study was to establish if medical treatment and respiratory rehabilitation in COPD used simultaneously lead to the greater improvement of PaO2, PaCO2 and physical condition and decreaseing dyspnea than medical treatment alone. Methods. A total of 60 patients divided into three groups according to the severity of obstruction (mild - I, severe - II, very severe - III) were tested. Each group had the two subgroups of patients - first one with those treated both with medical treatment and respiratory rehabilitation (A) and the second one with the patients treated only with medical treatment (B). The treatment took 21 days. The measurements of PaO2 and PaCO2) intensity of dyspnea at rest and exercise (10 - point Borg Category Scale), and physical capacity (Six-Minute Walk Test - 6MWT) were done on the first and on the last day of testing. Results. The results showed that all of the patients who were treated with the combination of medical treatment and respiratory rehabilitation had significantly higher increase in the values of PaO2 (I - p < 0.01; II - p < 0.05; III - p < 0.01), score of Borg's scale (I - p < 0.05, p < 0.001; II - p < 0.05, p < 0.001; III - p < 0.001, p < 0.001) and 6MWT (I - p < 0.001; II - p < 0.001; III - p < 0.001), and that statistically significant increase of the values of PaCO2 (p < 0.05) had only the patients with very severe COPD treated with the combination of drugs and respiratory rehabilitation. Conclusion. Based on the obtained results we conclude that using respiratory rehabilitation in combination with pharmacological treatment of COPD gives statistically higher improvement of values of PaO2 and PaCO2, and physical condition, and also leads to decrease of intensity of dyspnea than using just drug therapy.